Evaluation of Euglena gracilis 815 as a New Candidate for Biodiesel Production - Chen, Zixi; Chen, Yehua; Zhang, Hua; Qin, Huan; He, Jiayi; Zheng, Zezhou; Zhao, Liqing; Lei, Anping; Wang, Jiangxin (Frontiers in Bioengineering and Biotechnology, 2022)
Euglena comprises over 200 species, of which Euglena gracilis is a model organism with a relatively high fatty acid content, making it an excellent potential source of biofuel. In this study, a new strain named E. gracilis 815 were isolated and characterized. E. gracilis 815 cells were cultivated under light and dark conditions, with either ethanol or glucose as an external carbon source and an autotrophic medium as control. To achieve maximum yields of active substances within a short period (i.e., six days), the effects of the light condition and carbon source on the accumulation of bioactive ingredients of E. gracilis 815 were explored, especially fatty acids. In comparison with the industrially used E. gracilis Z strain, our results showed that E. gracilis 815 exhibited high adaptability to different carbon sources and light conditions, with a high growth rate and lipid yield. We further determined the composition and content of fatty acids of E. gracilis 815 to assess its potential for biodiesel use. Our results suggested that E. gracilis 815 has excellent biodiesel potential under glucose addition in dark culture conditions, and could be a promising source for producing unsaturated fatty acids. Therefore, E. gracilis 815 is an excellent candidate for short-chain jet fuel, with prospects for a wide variety of applications.